Vikings. Season 6, Volume 2 [videorecording (DVD)] - Hirst, Michael, 1952- (Warner Bros. Entertainment Inc., 2022)
Season Six returns following the battle between brothers which left Bjorn Ironsides a hero to the people who have been under the tyrannical rule of Ivar for so long. As the new leader of Kattegat, Bjorn struggles to fill his late father's shoes as king, while facing critical dilemmas and wrestling with the idea that power overshadows morals. Meanwhile, Ivar travels to Russia and meets his match in Prince Oleg, a ruthless and unpredictable ruler.